Two component injection moulding of bi-material of stainless steel and yttria stabilized zirconia – green part - Emeka, Ukwueze Bonaventure; Abu Bakar Sulong,; Norhamidi Muhamad,; Zainuddin Sajuri,; Farrahshaida Salleh, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The two component injection molding (2C-PIM) is a promising technique for production of small, complex and high density, metal-ceramic parts in large scales. This method is a viable option for integrating incompatible functions or properties of the materials in a singular part or component. Thus, the production of near net shaped components via 2C-PIM is imperative due to cost effectiveness resulting from high unit volumes. In this study, the feasibility of joining stainless steel (17-4PH) and 3mol% yttria stabilized zirconia (3YSZ) materials in their green states was investigated. Two feedstock of SS17-4PH and 3YSZ powder materials was prepared based on optimum solid loading of 3vol% lower than value of the critical loading. The critical solid loading for the SS17-4PH and 3YSZ powder materials were 71vol% and 53vol% respectively, based on the oil absorption technique ASTM: D-281-12. The binder system utilized comprises of 60wt.% palm stearin (PS) and 40wt.% low density polyethylene (LDPE). The two materials were injected sequentially using the screw type injection molding machine (BOY 22A) to form a bi-material component. The green properties were investigated. The morphology of the individual green parts and composites depicted that the powders were optimally dispersed in the binder matrix indicating good mixture and compaction of the green components. The flexural strength of the single components of the bi-material was above 5 MPa. The strength of the bonding zone which was 1.4 MPa indicates an evidence of bonding.